Direksi Asing, Ukuran Perusahaan dan Penghindaran Pajak dengan Direktur Wanita Sebagai Variabel Pemoderasi - Setiadi, Nyimas Belinda Thania; Widaningsih, Desti Sri; Erlita, Winda; Hatta Hambali, Atika Jauharia (E-Jurnal Akuntansi, 2023)
Tax avoidance will result in reduced state revenues which can hinder national development. This study aims to determine the effect of foreign directors and company size on tax avoidance with female directors as a moderating variable. The nature of women who prefer to avoid risks and comply with regulations can influence decision making related to company policies. The research sample was obtained from the annual reports of manufacturing companies listed on the Indonesia Stock Exchange for the period 2015 - 2019 totaling 172 companies. The sampling technique was carried out by purposive sampling. By using panel data regression and moderated regression analysis, the result is that foreign directors have a negative effect on tax evasion, while firm size has a positive effect on tax evasion. In addition, female directors are not proven to be able to strengthen the influence of foreign directors and weaken the effect of company size on tax evasion. Thus, the number of female directors does not influence the decision to avoid tax. Keywords: Foreign Directors; Firm Size; Female Directors; Tax Avoidance